REVIEW OF NORTH CAUCASUS’ MINERAL WATER FIELD’S MODELING METHODS - K. V. Martirosyan; A. V. Martirosyan (Современная наука и инновации, 2022)
In this work the analysis of a number of the geofiltrational models constructed in relation to mineral water fields of the Caucasus Mineral Waters region is carried out. At the model’s creation of the data on mineral water production from Kislovodsk and Georgievsk fields was used.